A New Approach for the Solution of the Electrostatic Potential Differential Equations. (10th December 2009) - Awawdeh, Fadi; Khandaqji, M.; Mustafa, Z.
Abstract : This paper is focused on deriving an explicit analytical solution for the prediction of the electrostatic potential, commonly used on electrokinetic research and its related applications. Different from all other analytic techniques, this approach provides a simple way to ensure the convergence of series of solution so that one can always get accurate enough approximations. This new approach can be a useful tool in electrical field applications such as the separation of a mixture of macromolecules and the removal of contaminants in soil cleaning processes.